Conservative Muslims in Indonesia’s religious and political landscapes: Ahok’s blasphemy case as a political leverage - Imam Yahya; Sulistiyono Susilo (Cogent Social Sciences, 2024)
This study aims to examine how Islamist groups employ the fatwas issued by the Majelis Ulama Indonesia/MUI (Indonesian Ulema Council) as a means of political leverage. Specifically, the analysis is based on 2016’s MUI blasphemy fatwa case involving the former Jakarta Governor, Basuki Tjahaja Purnama (Ahok). Through a qualitative and sociological approach in analyzing politics and religious issues, this research reveals that the 2016 religious blasphemy fatwa in the case of Ahok is more politically motivated. Historically, this fatwa deviates from the traditional approach of MUI, which primarily emphasizes the strengthening of Islamic law with a focus on adherence to Islamic norms. The results also indicate that while fatwas concerning political issues and blasphemy have been issued by the MUI since its establishment in 1975, Ahok’s case has become a crucial political tool for these groups. The fatwa has placed MUI further into the realm of Indonesian politics than it had previously been. The establishment of Gerakan Nasional Pengawal Fatwa/GNPF-MUI (MUI National Fatwa Guard Movement) has been instrumental in shaping the 2017’s North Jakarta District Court decision of the blasphemy case, solidifying its status as a significant developing political entity. It has allowed them to align with opposition political parties and candidates during 2017 Jakarta gubernatorial and 2019 presidential elections and to oppose current government policies. Additionally, the study identifies justifications for employing fatwas as practical political tools, including the development of fatwa models that address practical political issues and changes in Indonesian politics that increasingly recognize the power of Islamic groups in election contests. MUI has a flexible role in society with some affiliating with the government, and others operating as a civil organization from a social perspective. This ambiguous position in MUI’s hierarchy permits the institution to serve as a justification tool for the government or a political tool for the opposition, depending on the situation.